Bath-Ambience-A mechatronic system for assisting the caregivers of bedridden people - Bezerra, Karolina (2017)
The health of older people is receiving special attention and dedication nowadays, with the aim of increasing their general wellbeing and quality of life. Studies into different aspects of the care of the elderly have found that emphasis should be given to solving problems related to bathing in different situations and environments. In particular, it is important to develop new assistive technologies to streamline and ease the burden of a caregiver's daily tasks. Generally-speaking, in the case of bedridden patients, bathing is typically carried out manually by a caregiver, using towels, sponges, and a water basin. Nevertheless, this apparently simple task needs some precautions in order to avoid the risk of microbial infections, falls and other injuries. With that in mind, this paper presents the design of a portable washing system, called Bath-Ambience, which enables bedridden patients to be bathed efficiently without having to be moved from their position. This portable system can be installed in different situations, both in a domestic setting, and in specialized institutions, and allows the caregiver to perform the bathing tasks without compromising health and safety, thereby making it possible to offer a comfortable and hygienic procedure to patients, improving their quality of life. This paper presents the design of the portable Bath-Ambience washing system, which provides efficient assistance for bathing bedridden patients without moving them to another place. This system is mainly dedicated for integration a smart home application in to allow bathing everywhere.